Correction: Tick cysteine protease inhibitors suppress immune responses in mannan-induced psoriasis-like inflammation - Wu, Huimei; Jmel, Mohamed Amine; Chai, Jinwei; Tian, Maolin; Xu, Xueqing; Hui, Yuan; Nandakumar, Kutty Selva; Kotsyfakis, Michail (Frontiers in immunology, 2025)
[This corrects the article DOI: 10.3389/fimmu.2024.1344878.].
Keywords: protease inhibitors; psoriasis; tick; immune responses; autoimmune disease